A 1, 2, 3, 4‐Tetrahydrofullerene Derivative Generated from a [60]Fulleroindoline: Regioselective Electrosynthesis and Computational Study. Issue 8 (17th June 2014) - Xiao, Yang; Wang, Guanwu
Abstract A 1, 2, 3, 4‐tetrahydro[60]fullerene with a five‐membered heterocycle fused to a [5, 6] junction was obtained with high regioselectivity by electrochemical functionalization of a [60]fulleroindoline. The structure was determined by spectroscopic data. A plausible reaction mechanism supported by computational calculations is proposed.